THE INFLUENCE OF TECHNOLOGICAL PARAMETERS OF LASER SURFACING ON THE PROPERTIES OF NiCrBSiC-WC COMPOSITES - A. E. Zatoka; D. V. Drobot; S. P. Merchev; S. V. Nevezhin; A. S. Gerasimov; D. А. Ronzhin (Тонкие химические технологии)
It was investigated the influence of technological parameters of laser cladding on the thickness of the carbide composite coatings with similar composition and properties of matrix and different types of reinforcing inclusions (spherical tungsten carbides (WC) and recycled carbides). Special attention is paid to physical-mechanical and service properties of the composites such as hardness and resistance to abrasive wear. It is established that the thickness of the carbide composite coatings increases with increasing laser power and flow rate of the carrier gas, and with decreasing speed of the laser and the step of cladding. The study showed that at the addition of 50 wt.% WC matrix has smaller hardness values 540-560 HV, which allows to obtain the structure of the carbide composite coatings without cracks. At the same time, at addition of 80 wt.% WC matrix has higher hardness 670 HV, which does not provide the structure without cracks. Resistance of composites NiCrBSiC-WC to cracking, as well as their wear resistance, increases with increasing content of tungsten carbide. The wear resistance of the coatings received from powder Technicord 655-SL, with a reinforcement by recycled carbide, comparable to that for coatings from spherical tungsten carbide Tekmat WC-125. Coatings NiCrBSiCWC, obtained by laser cladding, are used to increase the service life of the equipment telemetering systems, in particular, it is possible to prevent of abrasion and provide of increasing the service life of the contact pads of the equipment for measurement while drilling.